3. Упростите выражение: а) (sin⁡α/(1+cos⁡α )+sin⁡α/(1-cos⁡α )) 1/(1+〖ctg〗^2 α)

ГАТИНЫ ГАТИНЫ    1   23.04.2022 22:55    15

Ответы
ggwp49 ggwp49  23.04.2022 23:00

2sina

(\frac{sina}{1+cosa}+\frac{sina}{1-cosa})*\frac{1}{1+ctg^2a}==\frac{sina(1-cosa)+sina(1+cosa)}{(1+cosa)(1-cosa)}*\frac{1}{1+ctg^2a}==\frac{sina(1-cosa+1+cosa)}{1-cos^2a}*\frac{1}{1+\frac{cos^2a}{sin^2a}}==\frac{sina*2}{sin^2a}*\frac{1}{\frac{sin^2a+cos^2a}{sin^2a}}==\frac{2}{sina}*\frac{sin^2a}{1}=2sina

Формулы для решения:

sin^2a+cos^2a=1sin^2a=1-cos^2actga=\frac{cosa}{sina}

(a-b)(a+b)=a^2-b^2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра